Biossorção de íons metálicos em águas utilizando casca de pinus como material adsorvente alternativo - Strey, Leonardo (2013)
This work proposes the use of the bark of Pinus elliottii, a residue of wood processing, as biosorbent in the removal of metal ions Cd2+, Pb2+ and Cr3+solutions fortified, as an alternative to conventional treatment methods, such as precipitation, ion exchange, electrochemical treatment, flocculation and filtration. The biosorbent was characterized by scanning electron microscopy (SEM), infrared spectroscopy (FT-IR) and point of zero charge (pHPCZ). Adsorption tests were performed aiming to determine the optimal conditions of pH, mass of adsorbent and contact time for the adsorption process. The adsorption kinetics was evaluated by pseudofirst and pseudosecond order models, Elovich and intraparticle diffusion. Adsorption isotherms for each metal were constructed, which were linearized according to mathematical models of Langmuir, Freundlich and Dubinin-Radusckevich. To compare this biosorbent with a commercial adsorbent, comparative studies with activated charcoal were performed . Furthermore, we evaluated the ability of desorption of materials and the influence of temperature on adsorption of metals studied by pine bark. The characterization of the biosorbent by SEM showed a rough and heterogeneous surface, important adsorption characteristics. From the FT-IR was identified compounds such as lignin, cellulose and hemicellulose, which favor the adsorption process. The pHPZC obtained was 3.5. The mass tests showed that 8 g L-1 biosorbent are sufficient for efficient removal of metal ions in solution. From the tests of pH, optimum conditions were obtained: 7.0 for Cd and 5.0 to Pb and Cr. The equilibrium time for adsorptive process were 40, 20 and 80 min for Cd, Pb and Cr, respectively. With the application of kinetic models is possible to suggest that the main limiting step for adsorption of these metal ions may be the chemisorption. The mathematical models that best fitted for the adsorption pine bark were Dubinin-Radushkevich for Cd, Freundlich for Pb, and Langmuir and Freundlich for Cr. The increase in temperature increased removal efficiency and, furthermore, with the thermodynamic parameters, it was found that the adsorption process is controlled by chemisorption. Desorption values were low, indicating a strong interaction of the metal with the surface of the adsorbent. In comparative studies with activated coal its possible to concluded that, despite the bark of Pinus elliottii present an adsorption efficiency less than this, the same satisfactory results of adsorption and removal of metal ions present in solutions fortified. Thus, it is concluded that the use of the bark of Pinus elliottii as biosorbents showed a promising alternative for the decontamination of contaminated water bodies by metal ions Cd, Pb and Cr